Eastern Kenya Landscapes - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
These are photos of one of the semi-arid areas of Kenya, during the rainy season taken to contrast the upcoming dry spell in August. Photo: Olive Thiongo'o (CCAFS).